Sex Determination by Two Y-Linked Genes in Garden Asparagus. Issue 6 (27th March 2020) - Harkess, Alex; Huang, Kun; van der Hulst, Ron; Tissen, Bart; Caplan, Jeffrey L.; Koppula, Aakash; Batish, Mona; Meyers, Blake C.; Leebens-Mack, Jim
Abstract : Y chromosome in garden asparagus determines sex via two Y-linked genes, one that suppresses female pistil development and another that promotes male anther development. Abstract: The origin and early evolution of sex chromosomes have been hypothesized to involve the linkage of factors with antagonistic effects on male and female function. Garden asparagus ( Asparagus officinalis ) is an ideal species to investigate this hypothesis, as the X and Y chromosomes are cytologically homomorphic and evolved from an ancestral autosome pair in association with a shift from hermaphroditism to dioecy. Mutagenesis screens paired with single-molecule fluorescence in situ hybridization directly implicate Y-specific genes that respectively suppress female (pistil) development and are necessary for male (anther) development. Comparison of contiguous X and Y chromosome assemblies shows that hemizygosity underlies the loss of recombination between the genes suppressing female organogenesis ( SUPPRESSOR OF FEMALE FUNCTION ) and promoting male function ( TAPETAL DEVELOPMENT AND FUNCTION1 [ aspTDF1 ]). We also experimentally demonstrate the function of aspTDF1. These findings provide direct evidence that sex chromosomes can function through linkage of two sex determination genes.